2007
DOI: 10.1002/hup.844
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dose initiation of quetiapine for the treatment of acute schizophrenia and schizoaffective disorder: a randomised, multicentre, parallel‐group, open study

Abstract: A higher proportion of patients experienced AEs with rapid initiation of quetiapine (800 mg/day by Day 4), although withdrawals due to AEs were comparable. Rapid initiation of quetiapine was generally well tolerated and effective in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…These results are supported by another, larger, multicentre study in 269 hospitalised patients with schizophrenia or schizoaffective disorder which used the same dosing regimens as above for rapid and standard initiation [43]. In this study, rapid initiation of quetiapine was well tolerated, with no serious AEs, and there was no significant difference in the numbers of patient discontinuations due to AEs at Day 7 in the rapid and standard initiation groups (n 0/ 3 and n 0/ 2, respectively).…”
Section: Appropriate Dosing In the Acute Settingsupporting
confidence: 68%
See 1 more Smart Citation
“…These results are supported by another, larger, multicentre study in 269 hospitalised patients with schizophrenia or schizoaffective disorder which used the same dosing regimens as above for rapid and standard initiation [43]. In this study, rapid initiation of quetiapine was well tolerated, with no serious AEs, and there was no significant difference in the numbers of patient discontinuations due to AEs at Day 7 in the rapid and standard initiation groups (n 0/ 3 and n 0/ 2, respectively).…”
Section: Appropriate Dosing In the Acute Settingsupporting
confidence: 68%
“…One small study reported a higher incidence of orthostatic hypotension, but this was comparable between rapid (2/13 patients; 15.4%) and standard (1/7 patients; 14.3%) initiation groups [46]. In summary, although outside current prescribing information guidance, clinical experience and results from rapid initiation studies indicate that, in hospitalised patients with acute schizophrenia or bipolar mania, quetiapine can be initiated at 200 mg and the dose increased in increments of 200 mg/day to reach 800 mg by Day 4 (Figure 3) [42,43,46,47]. An alternative dosing regimen based on clinical experience has also been suggested for investigation in future clinical trials (N. Keks, personal communication).…”
Section: Appropriate Dosing In the Acute Settingmentioning
confidence: 99%
“…Quetiapine can be initiated at a dosage of 100 mg twice daily with subsequent dosage increases of 200 mg/day. [92][93][94] Olanzapine [95,96] and risperidone [97] may also be safely initiated with as much as 40 mg/day and 6 mg/day, respectively, in divided doses.…”
Section: Antipsychotic Reinitiationmentioning
confidence: 99%
“…Support for this strategy comes from the evaluation of protocols for rapid initial dose escalation of atypical antipsychotics. In these studies, rapid titration of quetiapine (up to 800 mg/day in 4 days [92][93][94] ), olanzapine (up to 40 mg in the first 24 hours [95,96] ) and risperidone (up to 6 mg in the first 24 hours [97] ) was possible with the use of multiple daily dosing regimens.…”
Section: Antipsychotic Dosing Frequencymentioning
confidence: 99%
“…Orthostatic hypotension, dizziness, and syncope are of specific concern during rapid titration of quetiapine 74. In the post-hoc analysis, the incidence of these events was low during the first week of treatment, supporting rapid initiation 73…”
Section: Safety and Tolerabilitymentioning
confidence: 87%